Direct Reprogramming Rather than iPSC-Based Reprogramming Maintains Aging Hallmarks in Human Motor Neurons - Tang, Yu; Liu, Meng-Lu; Zang, Tong; Zhang, Chun-Li (Frontiers in Molecular Neuroscience, 2017)
In vitro generation of motor neurons (MNs) is a promising approach for modeling motor neuron diseases such as amyotrophic lateral sclerosis (ALS). As aging is a leading risk factor for the development of neurodegeneration, it is important to recapitulate age-related characteristics by using MNs at pathogenic ages. So far, cell reprogramming through induced pluripotent stem cells (iPSCs) and direct reprogramming from primary fibroblasts are two major strategies to obtain populations of MNs. While iPSC generation must go across the epigenetic landscape towards the pluripotent state, directly converted MNs might have the advantage of preserving aging-associated features from fibroblast donors. In this study, we confirmed that human iPSCs reset the aging status derived from their old donors, such as telomere attrition and cellular senescence. We then applied a set of transcription factors to induce MNs from either primary fibroblasts or iPSC-derived neural progenitor cells. The results revealed that directly reprogrammed MNs, rather than iPSC-derived MNs, maintained the aging hallmarks of old donors, including extensive DNA damage, loss of heterochromatin and nuclear organization, and increased SA-β-Gal activity. iPSC-derived MNs did not regain those aging memories from old donors. Collectively, our study indicates rejuvenation in the iPSC-based model, as well as aging maintenance in direct reprogramming of MNs. As such, the directly reprogrammed MNs may be more suitable for modeling the late-onset pathogenesis of motor neuron diseases.